Museum Presentations for Older Adults: A Review of Universal Design for Learning (UDL) Integration with Digital Storytelling (DST) Guidelines - Kittichai Kasemsarn; Farnaz Nickpour (Heritage, 2025)
Museums face significant challenges in engaging older adult visitors, particularly regarding digital storytelling (DST) integration and technology accessibility. In this case, universal design for learning (UDL) principles could address accessibility and engagement challenges for older adult visitors through multiple means of representation, engagement, and expression. This review examines how museums can develop inclusive DST frameworks that integrate universal design for learning (UDL) principles to enhance older adults’ engagement and learning experiences. The study investigates three main factors, namely DST, UDL, and older adults’ specific needs and preferences in museum contexts. Through a comprehensive literature review, this research presents an initial framework that systematically maps 10 DST elements across UDL’s 3 core principles, namely multiple means of engagement, representation, and action/expression. The initial framework contributes new knowledge by offering practical implementation strategies while establishing a theoretical foundation for understanding how DST can be adapted to serve older adults’ needs. This review article advances museum accessibility studies and provides a foundation for developing more inclusive cultural institutions that effectively serve older adult visitors while maintaining engaging and meaningful experiences.
Keywords: Digital Storytelling and Education; Subtitles and Audiovisual Media; Museums and Cultural Heritage